2011
DOI: 10.1002/gcc.20869
|View full text |Cite
|
Sign up to set email alerts
|

Let‐7 MicroRNA and HMGA2 levels of expression are not inversely linked in adipocytic tumors: Analysis of 56 lipomas and liposarcomas with molecular cytogenetic data

Abstract: The aim of our study was first to assess the role of HMGA2 expression in the pathogenesis of adipocytic tumors (AT) and, second, to seek a potential correlation between overexpression of HMGA2 and let-7 expression inhibition by analyzing a series of 56 benign and malignant AT with molecular cytogenetic data. We measured the levels of expression of HMGA2 mRNA and of eight members of the let-7 microRNA family using quantitative RT-PCR and expression of HMGA2 protein using immunohistochemistry. HMGA2 was highly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
4
17
1
Order By: Relevance
“…When we started this study, information about the genomic status of HMGA2 in liposarcoma was scarce. A high frequency of the amplification of HMGA2 in well-differentiated liposarcoma had indeed been reported by our group 5,19 and by others. 6,10,21 Altogether, the available data had been obtained by heterogeneous methods including FISH, 5,19,22 qRT-PCR, 19 Southern blotting, 21 or CGH, 6 and the total number of patients studied was small.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…When we started this study, information about the genomic status of HMGA2 in liposarcoma was scarce. A high frequency of the amplification of HMGA2 in well-differentiated liposarcoma had indeed been reported by our group 5,19 and by others. 6,10,21 Altogether, the available data had been obtained by heterogeneous methods including FISH, 5,19,22 qRT-PCR, 19 Southern blotting, 21 or CGH, 6 and the total number of patients studied was small.…”
Section: Discussionsupporting
confidence: 82%
“…A high frequency of the amplification of HMGA2 in well-differentiated liposarcoma had indeed been reported by our group 5,19 and by others. 6,10,21 Altogether, the available data had been obtained by heterogeneous methods including FISH, 5,19,22 qRT-PCR, 19 Southern blotting, 21 or CGH, 6 and the total number of patients studied was small. Here, we used FISH in a large series of 116 atypical lipomatous tumors/well-differentiated liposarcomas and dedifferentiated liposarcomas and we demonstrated that amplification of HMGA2 was significantly associated with atypical lipomatous tumor/well-differentiated liposarcoma, whereas the absence of amplification of HMGA2 was associated with dedifferentiated liposarcoma.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations